HER-STORIES IN SOUTH AFRICAN SPORT: GENDER AND SPORT IN THE CAPE COLONY 1806-1910 - Jones, Denise (Journal of Community and Health Sciences, 2020)
Introduction: The gendering of South African sport has a point of origin which is not explicitly evident until one examines the impact of the combined effects of the masculinity-sports relationship during the Victorian era, British imperialism and colonization in Southern Africa, and the institutionalisation of sports in England and her colonies. The question that emerges is "how did this shape the sports(s) practices of women at the time?" Objectives: The objective is to highlight the way the sporting culture of Victorian England and the associated ideals of womanliness and manliness shaped the initial construction of gender and sport in South Africa. Methods: Review of literature on sport in the history of South Africa, 1806-1910. The article has been written within the framework of subsequent emerging themes. Discussion: In this article the focus is on (1) the way the importance placed on the reproductive role of women promoted the view that females were physically more vulnerable than males and therefore their participation in sports put them at risk; (2) how female sports participation was both liberating and restrictive and led to redefinition of femininity; and (3) the scant reference to sporting females in the Cape media of the time. Implications for practice and research: It is not possible to obtain an understanding of the way sport constructs unequal gender relations without some knowledge of how they evolved over time. Scholarship in sports history should incorporate gender relations as an analytical category of historical research.